PATCH: posture and mobility training for care staff versus usual care in care homes: study protocol for a randomised controlled trial - Graham, Liz (Trials, 2018)
BACKGROUND: Residents of care homes have high levels of disability and poor mobility, but the promotion of health and wellbeing within care homes is poorly realised. Residents spend the majority of their time sedentary which leads to increased dependency and, coupled with poor postural management, can have many adverse outcomes including pressure sores, pain and reduced social interaction. The intervention being tested in this project (the Skilful Care Training Package) aims to increase the awareness and skills of care staff in relation to poor posture in the older, less mobile adult and highlight the benefits of activity, and how to skilfully assist activity, in this group to enable mobility and reduce falls risk. Feasibility work will be undertaken to inform the design of a definitive cluster randomised controlled trial. METHODS: This is a cluster randomised controlled feasibility trial, aiming to recruit at least 12–15 residents at each of 10 care homes across Yorkshire. Care homes will be randomly allocated on a 1:1 basis to receive either the Skilful Care Training Package alongside usual care or to continue to provide usual care alone. Assessments will be undertaken by blinded researchers with participating residents at baseline (before care home randomisation) and at three and six months post randomisation. Data relating to changes in physical activity, mobility, posture, mood and quality of life will be collected. Data at the level of the home will also be collected and will include staff experience of care and changes in the numbers and types of adverse events residents experience (for example, hospital admissions, falls). Details of NHS service usage will be collected to inform the economic analysis. An embedded process evaluation will explore intervention delivery and its acceptability to staff and residents. DISCUSSION: Participant uptake, engagement and retention are key feasibility outcomes. Exploration of barriers and facilitators to intervention delivery will inform intervention optimisation. Study results will inform progression to a definitive trial and add to the body of evidence for good practice in care home research. TRIAL REGISTRATION: ISRCTN Registry, ISRCTN50080330. Registered on 27 March 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-2863-5) contains supplementary material, which is available to authorized users.